Bakuman. 1, Dreams and reality - Ōba, Tsugumi; Obata, Takeshi, 1969-; Miyaki, Tetsuichiro (San Francisco : VIZ Media, 2010)
Moritaka Mashiro, who enjoys drawing, is encouraged by his classmate, aspiring writer Akito Takagi, to join forces to enter the professional world of manga, which leads Moritaka to wonder if he can elevate his skills and efforts to be a success.
Translated from the Japanese.
"First published in Japan in 2008 by Shueisha Inc., Tokyo"--P.facing t.p.
"This volume contains material that was originally published in English in Shonen Jump #89-91"--P. facing t.p.
"This book reads from right to left"--Cover p. [4].
Young Adult
Young Adult
Keywords: Artists -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc. -- Japan -- Comic books, strips, etc. -- Fiction; Drawing -- Comic books, strips, etc. -- Fiction; Artists -- Comic books, strips, etc. -- Fiction; Manga -- Comic books, strips, etc. -- Fiction; Drawing -- Comic books, strips, etc. -- Fiction; Manga; Comic books, strips, etc; Graphic novels; Graphic novels